2007
DOI: 10.1158/0008-5472.can-07-0098
|View full text |Cite|
|
Sign up to set email alerts
|

Intratumoral Delivery and Suppression of Prostate Tumor Growth by AttenuatedSalmonella entericaserovartyphimuriumCarrying Plasmid-Based Small Interfering RNAs

Abstract: The facultative anaerobic, invasive Salmonella enterica serovar typhimurium (S. typhimurium) has been shown to retard the growth of established tumors. We wondered if a more effective antitumor response could be achieved in vivo if these bacteria were used as tools for delivering specific molecular antitumor therapeutics. Constitutively activated transcription factor signal transducer and activator of transcription 3 (STAT3) promotes the survival of a number of human tumors. In this study, we investigated the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 45 publications
2
83
1
Order By: Relevance
“…In fact, attenuated Salmonella vectors have already been applied in vivo for the treatment of some malignancies, such as PCa. 24 Further efforts are clearly necessary for exploring the therapeutic value of parenteral administration of attenuated Salmonella carrying various anti-tumor therapies. In addition, the use of additional cell lines would be informative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, attenuated Salmonella vectors have already been applied in vivo for the treatment of some malignancies, such as PCa. 24 Further efforts are clearly necessary for exploring the therapeutic value of parenteral administration of attenuated Salmonella carrying various anti-tumor therapies. In addition, the use of additional cell lines would be informative.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuated S. typhimurium as a gene delivery vector provides more advantages when compared to viral vectors, such as good targeting. [24][25][26] For example, Salmonella can: (i) specifically colonize in hypoxic tumor tissues if administered through the intravenous or intraperitoneal routes; (ii) be used across a wide range of tissues; (iii) express foreign genes in any hypoxic region, unlike a retroviral vector which can only infect dividing cells; (iv) proliferate in vivo and efficiently express exogenous gene products; and by itself exerts antitumor effects; (v) be an ideal and safe vehicle for gene transfer since that it is sensitive to antibiotics and small doses of currently available antibiotics can kill it; and (vi) not be rejected by the host upon longterm use. Taken together, these characteristics make S. typhimurium an ideal vector for gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Primary tumour blocks (1.5 mm 3 ) were implanted into the right abdomens of C57BL/6 mice as previously described. 16 On day 5, tumours were visible at the sites of implantation (mean volume: 52.7612.1 mm 3 , n58). Cancer bearing mice were independently injected intratumourally with PBS, HAP-si-scramble or HAP-si-Stat3, which was repeated on day 20.…”
Section: Antitumour Activity Of Si-stat3mentioning
confidence: 96%
“…66 Combined oncolytic and siRNA therapy using systematically administered attenuated S. typhimurium expressing siRNA against tumor transcription factor STAT3 has also been evaluated. 67 Both of these studies demonstrated higher efficiency for combined therapy compared with treatment with nonRNAi-inducing bacteria. In addition to being used to produce and deliver silencing short-hairpin RNA, bacteria can also been exploited to deliver eukaryotic short-hairpin RNA-expression plasmids to mammalian tumor cells.…”
Section: Transkingdom Rnaimentioning
confidence: 99%